ADENOSINE ACTIVATES A2b RECEPTORS AND ENHANCES CHLORIDE SECRETION IN KIDNEY INNER MEDULLARY COLLECTING DUCT CELLS - Rajagopal, Madhumitha (2010)
In the kidney, defects in the regulation of urine salt excretion can result in extracellular fluid volume expansion, leading to salt-sensitive hypertension. Previous studies have demonstrated that when rats are maintained on a high sodium chloride (NaCl) diet, adenosine production increases in the renal medulla with parallel changes in adenosine receptor expression. These studies suggest that adenosine signaling in the kidney can respond to high NaCl loading; however, the functional consequences of these changes in adenosine signaling are not clear. We used the immortalized cell line mIMCD-K2, a murine model system for the renal inner medullary collecting duct (IMCD), to study the direct effects of adenosine on NaCl transport across IMCD epithelium with an Ussing chamber system. When epithelial Na(+) channels were inhibited, addition of adenosine to the apical side of mIMCD-K2 cell sheets stimulated short-circuit current (I(sc)) in a dose-dependent manner. This increase in I(sc) was inhibited by a CFTR Cl(−) channel inhibitor. Pharmacological studies with a panel of adenosine receptor agonists and antagonists demonstrated that adenosine activates apical A2b adenosine receptors to enhance I(sc). Furthermore, adenosine application to mIMCD-K2 cell sheets increased intracellular cAMP, while inhibition of protein kinase A (PKA) completely blocked the adenosine response. Together, our findings indicate that adenosine stimulates Cl(−) secretion through CFTR in mIMCD-K2 cells by activating apical A2b receptors and signaling through cAMP/PKA. We propose that this adenosine receptor pathway may provide one mechanism for enhancing urine NaCl excretion in the setting of high dietary NaCl intake.